Gamelan Touch as an Innovation of Regional Sound Arts Interactive Learning Media - Abdul Aman; Tri Joko Raharjo; M. Khafid; Teguh Supriyanto (International Conference on Science, Education, and Technology, 2023)
The 2013 and independent curricula provide a special domain for developing the region's potential where the education unit is located through local content subjects. Regional Voice Art or SSD is a local content that raises learning material for tembang macapat and tembang dolanan. The empirical reality in the field of SSD learning experiences many significant obstacles. From discussions with several fellow teachers through the KKG forum, it was found that teachers still had difficulty teaching this SSD material. Some fellow teachers have difficulty developing teaching materials, so SSD subjects are rarely taught. It is quite difficult if there are no tools to teach tembang macapat or tembang dolanan. The tones used for these songs are not solemnized tones but use slendro and pelog gamelan tunings. The existence of gamelan in the researcher's school and surrounding environment is still rare. Given that gamelan is also not cheap, so for small schools and far from the city will be an obstacle for the school. Based on these conditions, the author made an innovative media with gamelan touch or gasen. The process of making this touch gamelan by utilizing plywood to be designed into a gamelan shape and connected to a chip programmed on a computer. It is utilized as an SSD learning media. This media is then distributed to teachers in the Teacher Working Group forum to be disseminated and utilized in helping teach regional sound art materials (SSD).